LAO P.D.R. : Assessing the Quality of Trade Statistics - Bannister, Geoffrey (IMF Working Papers; Working Paper ;, 2017)
This paper assesses external trade statistics in Lao PDR by looking at mirror statistics, and with reference to international experience in compilation and dissemination of external trade data. We find that exports could be underreported by 8 to 50 percent, while imports could be underreported by 30 to 70 percent, and the trade deficit could be 20 percent to 280 percent higher. Underreporting is concentrated in trade with major partners, including Thailand (17 percent of total trade), China (10 percent of total trade) and Vietnam (3 percent of total trade). On the export side, underreporting is concentrated in wood and wood products, while for imports it is concentrated in a much wider variety of products, including food, fuel, vehicles, machinery, chemical products, plastics and rubber, and construction materials. Possible sources and implications of these discrepancies are discussed.